1998
DOI: 10.1136/hrt.80.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Direct current cardioversion does not cause cardiac damage: evidence from cardiac troponin T estimation

Abstract: Aim-To determine whether elective direct current (dc) cardioversion of atrial fibrillation/flutter causes myocardial damage. Methods and results-Cardiac troponin T and creatine kinase were estimated 20-28 hours after dc cardioversion in 51 patients who received dc shocks for elective cardioversion of chronic atrial fibrillation/ flutter. Although creatine kinase was raised in 44 patients, cardiac troponin T was undetectable in all patients. Conclusion-Cardiac damage does not occur as a result of cardioversion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Previous studies were conducted in a small number of patients, and inclusion/exclusion criteria often were not strict; our results confirm those described in some previous studies. 1,[9][10][11][12][13][14] On the other hand, our findings are discordant with those of other studies involving smaller series of patients, demonstrating the presence of mild myocardial injury in some patients after elective EEC for AF. [4][5][6][7][8] Differences in inclusion criteria may account for the discrepancies in the observed conclusions.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies were conducted in a small number of patients, and inclusion/exclusion criteria often were not strict; our results confirm those described in some previous studies. 1,[9][10][11][12][13][14] On the other hand, our findings are discordant with those of other studies involving smaller series of patients, demonstrating the presence of mild myocardial injury in some patients after elective EEC for AF. [4][5][6][7][8] Differences in inclusion criteria may account for the discrepancies in the observed conclusions.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, several workers have reported the detection of a mildly elevated level of cTnI or transient ST-segment elevation in some patients after elective EEC for AF, implying myocardial injury could have been caused by this procedure. [4][5][6][7][8] Other studies showed no change in serum levels of either troponin I or T. 1,[9][10][11][12][13][14] To our knowledge there has not been any study of sufficiently large size addressing the effects of EEC and myocardial damage. Moreover, most of the troponin studies have included clinically unstable patients with raised levels of the biochemical markers, and only a small proportion of patients with reduced ejection fraction (EF) was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although cTnT measurements have been used to indicate that direct-current cardioversion (DCCV) does not cause cardiac damage, 11 Roy and colleagues 12 reported that in patients with atrial fibrillation, IMA levels are significantly elevated at 1 and 6 hours after DCCV, especially in patients with electrocardiographic evidence of post-DCCV ischemia. Sinha and associates 13 evaluated ECG, cTnT and IMA levels individually and in combinations in patients diagnosed with non-ischemic chest pain, unstable angina and MI with ST-or non-ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…153,154 • Cardioversion, ablation and cardiac arrest: Elective electrical cardioversion in most patients does not result in troponin elevations. 155,156 When present, elevations are mild. 157,158 Elevations are more common in patients with cardiac arrest who have undergone direct-current shock (often multiple) or prolonged resuscitation, or both.…”
Section: Other Clinical Situations In Which Troponin Levels May Be Elmentioning
confidence: 99%